Empirical labor economics : the search approach - Devine, Theresa J. (OUP E-Books., 1991)
Presenting a complete survey of labor economics from the search point of view, this is the first book to coordinate a vast and scattered literature, making an increasingly important and sophisticated area in modern applied economics readily accessible. Completely comprehensive, Empirical Labor Economics covers not only sequential and random search, but all stochastic models of the labor market, and treats underlying economic theory and econometric methods as needed. It examines structural search models, studies directed at particular policy questions--such as the effect of unemployment benefit.